Anthropogenic fire patterns affect niche breadth and niche overlap in sympatric songbird species - Heim Wieland; Thomas Alexander; Berner Isabelle; Korschefsky Tim; Hölzel Norbert; Kamp Johannes (Elsevier B.V., 2022)
The severity of wildfires increases globally, and return intervals decrease. Fires can benefit biodiversity, as post-burn early successional stages provide diverse habitats and niches for many species. How fire disturbance affects niche use and niche overlap of species is poorly understood so far. We studied the effect of anthropogenic fire on breeding habitat use, niche breadth and niche overlap of five sympatric bunting species breeding in wetlands of the Amur River floodplain (Russian Far East). Fire frequency, measured as the time an area burnt in the period 2000 to 2017, was mapped from Landsat imagery and related to the presence or absence of the species. Niche breadth and niche overlap were calculated separately for occurrences in burned (within the study year) and unburned patches. Fire frequency characterized differences in niche use among the species, but the probability of presence was not affected by recent fire in four of five species. Niche breadth was significantly lower in recently burned patches, but we found no increase in niche overlap between species after fire. Instead, the studied species seemed to occupy similar patches before and after fire, possibly because of a high site fidelity. Our results clearly show that fire frequency is a major determinant for the niche separation in the five studied species, while recent fire does not affect niche overlap.